Jual Beli Handphone Bekas Perspektif Ekonomi Islam - Galuh Mustika Argarini; Faisol Mubarok (Journal of Economic and Islamic Research, 2022)
The need for communication resulted in the rapid sale and purchase of mobile phones. Used cellphones are half-used cellphones or have been used by the first consumer and have experienced a decline in quality. However, this does not affect consumer interest in buying used mobile phones because the prices are relatively cheaper. In the transaction of buying and selling activities can be said to be valid or not depending on the fulfillment of the pillars and conditions of the transaction. The purpose of this study is to describe the practice of buying and selling used mobile phones from an Islamic economic perspective. Based on the problems above, the type of research used is activities carried out within the community. Sources of data used are primary data sources, namely data sources obtained directly from the owner of the counter or sellers and buyers, secondary data sources, namely data sources obtained from records or books related to the problems that the author examines. The data collection method used is the method of observation, interviews and documentation.